Pengaruh Kualitas Produk, Harga dan Komunikasi WOM Terhadap Keputusan Pembelian Motor Trail Kawasaki Klx 150 (Studi Kasus Pada Konsumen Motor Trail Pada Sub Dealer UD. Delta Auto Motor Puruk Cahu) - Heni Rinawati; Hairudinor Hairudinor; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2019)
Quite high demand for Motorcycles Trail type in Puruk Cahu is inseparable from tofografi conditions Murung Raya District Region consisting of Mountains, most of the road that contacts between districts with other subdistricts still no road hardening and besides that at this time Sport Touring is also very loved By society. This can be seen by the total sales amount of 584 units of Kawasaki Trail Motorcycle KLX 150 since 2009 until 2016.This study aimed to examine the effect of Product Quality (X 1) Price (X 2) and Communications WOM (X 3) of the Purchase Decision on the User Motorcycle Trail KLX 150 in the area Kabupaten Murung Raya. Samples taken as many as 55 users Motorcycle Trail KLX 150 in the region Kabupaten Murung Raya saturated sampling technique. Collecting data using questionnaires, while data analysis using SPSS version 21 o'clock. The results of this study prove Product Quality (X 1) is partially significant effect on the purchase decision (Y) sig. 0,0001 and far-reaching 60,2% the, Price             (X 2) partially not significant effect on purchase decision (Y) sig. 0,705 and 6.5% big influence and Communication WOM (X 3) partially significant effect on the Purchase decision (Y) sig.0.023 and far-reaching 25.6%, while simultaneously e r Product Quality (X 1), Price (X 2) and Communications WOM (X3)  berp e been influence to purchase decision (Y) sig. 0,000 and far-reaching 47.5%. Implementation of this research that's improving Purchasing Decisions need to pay attention to product quality, price and Communications WOM. Keywords: Product Quality, Price, Communication WOM, Buying Decision